Molecular Building Kit of Fused-Proline-Derived Peptide Mimetics Allowing Specific Adjustment of the Dihedral Psi Angle - Einsiedel, Jürgen; Lanig, Harald; Waibel, Reiner; Gmeiner, Peter (Journal of Organic Chemistry, 2007)
(Chemical Equation Presented) Proline-derived peptide mimetics have become an area of paramount importance in peptide and protein chemistry. Since protein crystal structures frequently display Ψ angles of 140-170° for prolyl moieties, our intention was to design a completely novel series of 2,3-fused-proline-derived lactams covering this particular conformational space. Extending our recently described toolset of spirocyclic reverse-turn mimetics, we synthesized pyrrolidinyl-fused seven-, eight-, and nine-membered unsaturated lactam model peptides taking advantage of Grubbs' ring-closing metathesis. Investigating the seven-membered lactam 3a by means of IR and NMR spectroscopy and semiempirical molecular dynamics simulations, we could not observe a U-turn conformation; however, increasing the ring size to give eight- and nine-membered congeners revealed moderate and high type II β-turn inducing properties. Interestingly, the conformational properties of our model systems depend on both the ring size of the fused dehydro-Freidinger lactam and the position of the endocyclic double bond. Superior reverse-turn inducing properties could be observed for the fused azacyclononenone 3e. According to diagnostic transanular NOEs, a discrete folding principle of the lactam ring strongly deviating from the regioisomeric lactams 3c,f explains the conformational behavior. Hence, we were able to establish a molecular building kit that allows adjustments of a wide range of naturally occurring proline Ψ angles and thus can be exploited to probe molecular recognition and functional properties of biological systems. © 2007 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2007.nat.dchph.lphch.molecu